2014
DOI: 10.1074/jbc.m113.524611
|View full text |Cite
|
Sign up to set email alerts
|

ELIC-α7 Nicotinic Acetylcholine Receptor (α7nAChR) Chimeras Reveal a Prominent Role of the Extracellular-Transmembrane Domain Interface in Allosteric Modulation

Abstract: Background: Allosteric modulators bound to the transmembrane domain (TMD) of the ␣7 nicotinic acetylcholine receptor (␣7nAChR) can potentiate channel function. Results: ELIC-␣7nAChR showed potentiation only when the extracellular-transmembrane domain (ECD-TMD) interface matched that of ␣7nAChR. Conclusion: PAM modulation through the TMD requires a more specific ECD-TMD interface than agonist activation. Significance: The study provides insight into the basis for positive allosteric modulation of ␣7nAChR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 57 publications
2
40
0
Order By: Relevance
“…Single cysteine mutations were introduced using the same method used for the NMR samples. Preparation of RNA, expression in Xenopus laevis oocytes, and electrophysiology experiments were performed as previously reported (Pan et al, 2012a; Pan et al, 2012b; Tillman et al, 2013; Tillman et al, 2014). In order to ensure TET labeling does not destroy channel function, the purified TET-labeled ELIC was reconstituted into lipid vesicles as previously reported (Bondarenko et al, 2014) and injected into oocytes (50 nL; 2 mg/mL protein) for functional tests.…”
Section: Methodsmentioning
confidence: 99%
“…Single cysteine mutations were introduced using the same method used for the NMR samples. Preparation of RNA, expression in Xenopus laevis oocytes, and electrophysiology experiments were performed as previously reported (Pan et al, 2012a; Pan et al, 2012b; Tillman et al, 2013; Tillman et al, 2014). In order to ensure TET labeling does not destroy channel function, the purified TET-labeled ELIC was reconstituted into lipid vesicles as previously reported (Bondarenko et al, 2014) and injected into oocytes (50 nL; 2 mg/mL protein) for functional tests.…”
Section: Methodsmentioning
confidence: 99%
“…The early observation that the α 7 nAChR(ECD)-5HT 3 R(TMD+ICD) chimera was functional was the first evidence that the ECD and TMD may constitute independent tertiary modules (26). The α 7 nAChR(ECD)-α 1 GlyR(TMD+ICD) (18), the AChBP-5HT 3 (TMD+ICD) (29), and recently the ELIC(ECD)-α 7 nAChR(TMD) chimera (30) were subsequently reported to be functional, the ECD retaining "native-like" pharmacology for agonists and the TMD native-like channel selectivity. It is noteworthy that extensive mutations at the ECD-TMD interface were required to produce properly folded and/or functional AChBP-5HT 3 (TMD+ICD) and ELIC (ECD)-α 7 nAChR(TMD) chimeras.…”
Section: Discussionmentioning
confidence: 99%
“…These residues (L60, M63, E67, N75, N193, and E195) were evaluated along with several others in the surrounding region (Table 2). Figure 5 shows the residues in the gating interface with |ΔΔG| ≥ 0.5 kcal/mol (Hanek, et al, 2008; Tillman, et al, 2014). Tillman et al showed through chimera analysis that specific loops and linkers were necessary for PNU-120596 potentiation of α7 receptors (Tillman, et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 shows the residues in the gating interface with |ΔΔG| ≥ 0.5 kcal/mol (Hanek, et al, 2008; Tillman, et al, 2014). Tillman et al showed through chimera analysis that specific loops and linkers were necessary for PNU-120596 potentiation of α7 receptors (Tillman, et al, 2014). Here, we were able to isolate specific residues on some of these identified regions: in Loop 2, E67; in Loop 9, E195; and in the M2-M3 Linker, S287.…”
Section: Resultsmentioning
confidence: 99%